The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.05.04.490528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribotoxic collisions on CAG expansions disrupt proteostasis and stress responses in Huntington’s Disease

Abstract: Huntington's disease (HD) is a devastating neurodegenerative disorder caused by CAG trinucleotide repeat expansions encoding a polyglutamine (polyQ) tract in the Huntingtin (HTT) gene1. Although mutant HTT (mHTT) protein tends to aggregate, the exact causes of neurotoxicity in HD remain unclear2. Here we show that altered elongation kinetics on CAG expansions cause ribosome collisions that trigger ribotoxicity, proteotoxicity and maladaptive stress responses. CAG expansions cause an elongation rate conflict du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…There are also examples of pathological peptide repeat sequences that cause ribosome slowdown and premature termination which are not subject to the RQC pathway 66,69 . This includes Arg-Gly and Arg-Pro dipeptides from the C9ORF72 ORF, which cause amyotrophic lateral sclerosis and frontotemporal dementia 63,64 , and poly-glutamine repeats translated from CAG nucleotide repeat expansions in the mHtt gene, which cause Huntington's disease [77][78][79] . Interestingly, although the RQC pathway isn't demonstrated to act directly on these toxic repeats, expression of RQC pathway components is associated with lower disease severity in both instances 79,80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also examples of pathological peptide repeat sequences that cause ribosome slowdown and premature termination which are not subject to the RQC pathway 66,69 . This includes Arg-Gly and Arg-Pro dipeptides from the C9ORF72 ORF, which cause amyotrophic lateral sclerosis and frontotemporal dementia 63,64 , and poly-glutamine repeats translated from CAG nucleotide repeat expansions in the mHtt gene, which cause Huntington's disease [77][78][79] . Interestingly, although the RQC pathway isn't demonstrated to act directly on these toxic repeats, expression of RQC pathway components is associated with lower disease severity in both instances 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…This includes Arg-Gly and Arg-Pro dipeptides from the C9ORF72 ORF, which cause amyotrophic lateral sclerosis and frontotemporal dementia 63,64 , and poly-glutamine repeats translated from CAG nucleotide repeat expansions in the mHtt gene, which cause Huntington's disease [77][78][79] . Interestingly, although the RQC pathway isn't demonstrated to act directly on these toxic repeats, expression of RQC pathway components is associated with lower disease severity in both instances 79,80 . As the destabilizing peptide sequences we identify in this study cause ribosome slowdown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such widespread effects exist in the literature. For instance, Aviner et al (72) demonstrated that the ribosome collisions on mutant Huntington transcript produce a cycle of dysfunction that sequesters eIF5a, thereby depleting it from other transcripts and altering translation of stress-responsive transcripts, in part by misregulating their upstream open reading frames (uORFs). Interestingly, a recent preprint linked yeast gene copy number variation, Ssd1, and uORFs by suggesting that genes whose encoded mRNA abundance is substantially discordant with its protein abundance were more likely to contain uORFs, and that those reading frames were enriched for Ssd1 binding motifs (73).…”
Section: Discussionmentioning
confidence: 99%
“…Potent protein and ribosome quality control likely resolve colliding ribosomes in young, healthy cells. However, aging cells with disrupted proteostasis become more susceptible to elongation stalls and protein aggregation, exacerbating their toxic consequences (Aviner et al, 2022; Maity & Iben, 2022). Accordingly, mRNAs in aging cells have increased ribosome occupancy and ribosome collisions at inhibitory codon pairs which are previously shown to delay translation elongation (Stein et al, 2022).…”
Section: Rqc and Ngd Are Essential For Cellular Proteostasismentioning
confidence: 99%
“…The CGA repeat promotes RNA-based toxicity by increasing the probability of ribosome collisions due to an elongation rate conflict between Huntington's low translating portions of the mRNA. Moreover, mutant HTT protein also plays a role in translation failure since it sequesters translation factor eIF5A, promoting extensive ribosome stalling on hundreds of transcripts and causing widespread proteostasis breakdown (Aviner et al, 2022). Eventually, ribosome pausing and collisions occur across the transcriptome, altering the synthesis of essential proteostasis components such as ribosomes and proteasomes and deregulating stress responses.…”
Section: Rqc and Ngd Are Essential For Cellular Proteostasismentioning
confidence: 99%